2006
DOI: 10.1002/pola.21407
|View full text |Cite
|
Sign up to set email alerts
|

Reversible addition–fragmentation chain transfer polymerization of methyl methacrylate in emulsion

Abstract: Theoretical simulations showed that for controlled/living radical polymerization in an emulsion system, some of the earliest born particles could be superswollen to a size close to 1 lm. We hypothesized that the superswelling of these particles would lead to colloidal instability. Under the guidance of the simulation results, reversible addition-fragmentation chain transfer (RAFT) emulsion polymerization of methyl methacrylate (MMA) was carried out. Experimental results showed that increasing the initiation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 39 publications
7
66
1
Order By: Relevance
“…It has been reported that increasing the amount of surfactant could enhance the stability of RAFT polymerization in both emulsion and miniemulsion systems [21,32]. Considering this point, we increased the amount of SDS from original 0.25 g to 0.60 g (Exp.…”
Section: Comparison Of Polymerization Kinetics and Living Characters mentioning
confidence: 94%
“…It has been reported that increasing the amount of surfactant could enhance the stability of RAFT polymerization in both emulsion and miniemulsion systems [21,32]. Considering this point, we increased the amount of SDS from original 0.25 g to 0.60 g (Exp.…”
Section: Comparison Of Polymerization Kinetics and Living Characters mentioning
confidence: 94%
“…[135] [61] S/VBSC [62] 8* AN [63] (DBI) [64] DMAEMA [65] 9* (DBI) [64] DMAEMA [68] GMA [68] HPMAM/NMS [66] MMA [67] HEMA [68] (MA) [69] MMA [46,70,71] NIPAM [72] PFMA [73] (S) [44,74] S [75] S [76] S/AN [68] S/MAH [68] S S CN S S CN…”
Section: Characterization Of Raft-synthesized Polymersmentioning
confidence: 99%
“…A large number of recent studies relate RAFT polymerization in heterogeneous media (emulsion, [67,74,81,98,117,122,139,[161][162][163][164][165][166] miniemulsion, [10,76,[167][168][169][170][171][172][173][174][175] or suspension [176] ). The area has been reviewed by McCleary and Klumperman [11] and Save et al [177] 'Surfactant free' emulsion polymerization making use of a hydrophilic macroRAFT agent (typically based on PAA oligomer formed with RAFT agent 67) [117,161,163,164] has been used for BA [117] and styrene.…”
Section: Raft Polymerization In Heterogeneous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…LFRP techniques have also been extended to heterogeneous polymerizations such as emulsion and suspension polymerization. [8][9][10][11][12] LFRP with heterogeneous polymerization is an active research area as it provides a powerful tool for preparing tailor-made products and promises substantial practical applications. Three major LFRP techniques are nitroxide-mediated polymerization (NMP), 5 atom transfer radical polymerization (ATRP), 3 and reversible addition-fragmentation chain transfer (RAFT).…”
Section: Introductionmentioning
confidence: 99%